TCF7L2 regulates GPX4 to resist ferroptosis and enhance osteogenesis in mouse mesenchymal stem cells - Ming Lei; Boyu Liu; Baicheng Wan; Yanbin Feng; Yilin Teng; Deshuang Xi; Gaofeng Zeng; Shaohui Zong (European Journal of Medical Research)
Abstract Critical-sized bone defects, characterized by poor spontaneous healing capacity, remain a common clinical challenge, and stem cell and gene therapies are key strategies for bone repair and regeneration. Transcription factor 7-like 2 (TCF7L2) is a key regulator of the Wnt signaling pathway, with potential applications in gene editing. However, the role of TCF7L2 in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) remains poorly understood. We knocked down or overexpressed TCF7L2 to evaluate its effect on erastin-induced ferroptosis in BMSCs. Simultaneously, we assessed the impact of TCF7L2 overexpression on the osteogenic capacity of BMSCs. To confirm the involvement of glutathione peroxidase 4 (GPX4), we conducted rescue experiments by knocking down GPX4 expression. A mouse cranial defect model was established to analyze the effect of TCF7L2 overexpression on cranial bone healing. The results showed that TCF7L2 knockdown promoted, while TCF7L2 overexpression inhibited, erastin-induced ferroptosis in BMSCs. Mechanistic studies revealed that TCF7L2 knockdown reduced, while TCF7L2 overexpression enhanced, GPX4 expression, thereby regulating ferroptosis. Conversely, GPX4 knockdown significantly attenuated the regulatory effects of TCF7L2 overexpression on cell proliferation and ferroptosis inhibition. Furthermore, TCF7L2 overexpression promoted cell proliferation, osteogenic differentiation, and mineralization in vitro, while enhancing cranial defect healing in vivo. This study is the first to reveal the dual role of TCF7L2: regulating ferroptosis in BMSCs via GPX4, while promoting BMSC proliferation and osteogenic differentiation. These findings provide novel molecular targets and theoretical foundations for the treatment of bone defects.